EGHR: Efficient group-based handover authentication protocols for mMTC in 5G wireless networks. (15th January 2018) - Cao, Jin; Ma, Maode; Li, Hui; Fu, Yulong; Liu, Xuefeng
Abstract: Future fifth generation (5G) wireless network will be a flexible, open, and highly heterogeneous with densified small cell deployment and overlay coverage. The design of the access authentication for massive machine type communication (mMTC) devices in 5G heterogeneous networks is the challenging issue to achieve 5G applications security due to stringent latency and concurrent access requirements for 5G multi-tier architecture. The current roaming authentication mechanisms between Long Term Evolution-Advanced (LTE-A) network and Wireless Local Area Network (WLAN) proposed by 3GPP incur several protocol attacks with unacceptable delay for real-time mMTC applications. In this paper, we propose secure and efficient group-based handover authentication and re-authentication protocols for mMTC in 5G wireless networks when mMTC devices simultaneously roam into the new networks. Our proposed protocols outperform the standard mechanisms and other related protocols in terms of authentication signaling overhead and bandwidth consumption with robust handover security requirements. The BAN logic and the formal verification tool by using the AVISPA and SPAN show that our proposed protocols are secure against various malicious attacks.